Fluorescence detection of the nitric oxide-induced structural change at the putative nitric oxide sensing segment of TRPC5. Issue 8 (15th April 2020) - Tajima, Shunsuke; Nakata, Eiji; Sakaguchi, Reiko; Saimura, Masayuki; Mori, Yasuo; Morii, Takashi
Graphical abstract: Abstract: The plausible nitric oxide (NO)-sensing module of TRPC5 was incorporated in a enhanced green fluorescent protein (EGFP) to evaluate its conformational change as an optical response upon the reaction with NO. Two cysteine residues located in the NO-sensing module have been proposed to form a disulfide bond through S-nitrosylation of the thiol group by NO. Modification of the cysteine residues by NO resulted a ratiometric change of EGFP emission through transducing the conformational change of NO-sensing module to the EGFP chromophore. The oxidized form of NO-sensing module fused EGFP changed the intensity of emission spectra upon reduction of the disulfide bond at the NO-reactive module. The NO-sensing module fused EGFP in its reduced form avidly reacted with NO and realized the ratiometric fluorescence intensity changes depending on the formation of disulfide bond. These results support the notion that NO induces a conformational change at the putative NO-sensing segment of TRPC5, and provide a prototype for the genetically encoded cellular NO sensors.